2021
DOI: 10.3390/biom11020208
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Anti-HIV-1 Agents Based on HIV-1 Capsid Proteins

Abstract: The capsid of human immunodeficiency virus type 1 (HIV-1) is a shell that encloses viral RNA and is highly conserved among many strains of the virus. It forms a conical structure by assembling oligomers of capsid (CA) proteins. CA dysfunction is expected to be an important target of suppression of HIV-1 replication, and it is important to understand a new mechanism that could lead to the CA dysfunction. A drug targeting CA however, has not been developed to date. Hydrophobic interactions between two CA molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…A highly conserved Tryptophan (W)–Methionine (M) dipeptide (W184/M185) motif in H9 of CA CTD is engaged in hydrophobic interactions with the corresponding W184/M185 residues of a CA in a neighboring hexamer, at the twofold symmetry axis. Not surprisingly, mutations of these residues impair viral assembly [ 123 , 191 ]. A small molecule was selected by in silico screening as a peptidomimetic compound of W184/M185 in the interaction site.…”
Section: Site 3: the “Twofold” Binding Sitementioning
confidence: 99%
See 1 more Smart Citation
“…A highly conserved Tryptophan (W)–Methionine (M) dipeptide (W184/M185) motif in H9 of CA CTD is engaged in hydrophobic interactions with the corresponding W184/M185 residues of a CA in a neighboring hexamer, at the twofold symmetry axis. Not surprisingly, mutations of these residues impair viral assembly [ 123 , 191 ]. A small molecule was selected by in silico screening as a peptidomimetic compound of W184/M185 in the interaction site.…”
Section: Site 3: the “Twofold” Binding Sitementioning
confidence: 99%
“…Of note, the chirality of this molecule was important, as an MKN-1A diastereomer had decreased potency. Additionally, the trypsin-based indoyl and the methionine-based sulfidyl groups were essential for antiviral activity [ 191 ]. Hence, these efforts further confirmed that this site is a potential therapeutic target for subsequent drug design.…”
Section: Site 3: the “Twofold” Binding Sitementioning
confidence: 99%
“…This screening strategy provides some candidates with useful binding affinity, including MKN-1 (1) with a London dG value of −9.134, which had been found previously to have signicant anti-HIV activity. 75 This screening identied another candidate MKN-3 (2) with London dG value of −9.555, signifying a higher binding affinity for a CA molecule than that of MKN-1 (1). In the current study, MKN-3 (2) and several of its derivatives were synthesized, and their anti-HIV activity and cytotoxicity were evaluated.…”
Section: Introductionmentioning
confidence: 96%
“…Our strategy has involved design of small molecules, which might bind to the above site, using in silico screening. 75 Briey, a series of dipeptide mimics of Trp184 and Met185 were designed using the Molecular Operating Environment (MOE) (Chemical Computing Group Inc., Montreal, Quebec, Canada). The structure of one monomer molecule of the CA protein dimer (PDB ID: 3J34) remained as a receptor, and the backbone structure of Trp184 and Met185 of the other monomer molecule was removed.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of HIV to CA inhibitors requires mutations compromising the fitness of the virus, hence leading to a higher barrier to resistance and therapeutic efficiency. 10,11 So far, only a handful of capsid inhibitors are reported with benzodiazepine, 12 benzimidazole, 13 pyrrolopyrazolones, 14 furan, 15 and indole 16,17 scaffolds as in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%